A specialized bioengineering ion beam line - L. D. Yu (2018)
A specialized bioengineering ion beam line has recently been completed at Chiang Mai University to meet rapidly growing needs of research and application development in low-energy ion beam biotechnology. This beam line possesses special features: vertical main beam line, low-energy (30 keV) ion beams, double swerve of the beam, a fast pumped target chamber, and an in-situ atomic force microscope (AFM) system chamber. The whole beam line is situated in a bioclean environment, occupying two stories. The quality of the ion beam has been studied. It has proved that this beam line has significantly contributed to our research work on low-energy ion beam biotechnology. © 2007 Elsevier B.V. All rights reserved.